Sistem Pendukung Keputusan Menentukan Kelayakan Lahan Pembibitan Menggunakan Metode Multi Attribute Utility Theory - Juniar Hutagalung; Asyahri Nasyuha; Titin Pradita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Determining the location of plantation land is a very important role to support the development of oil palm plantations and also factors that support plantations to produce oil palm fruit with good quality. To help companies produce palm oil with the best quality fruit, it is necessary to have the appropriateness of the land used for oil palm planting from the seedling process. PT. Fajar Agung experienced several difficulties in making a decision to choose suitable land for oil palm seedlings, so making a decision took a long time. In determining the feasibility of oil palm nurseries, a decision support system is needed by applying the Multi Attribute Utility Theory (MAUT) method. The purpose of this study is to implement a decision support system in determining the feasibility of oil palm nurseries using the Multi Attribute Utility Theory (MAUT) method to be more effective and efficient for the leadership in making a decision so that the company does not suffer losses. From the calculation results to be used as an oil palm nursery with an assessment that is more than 0.500 which is declared feasible there are 6 alternatives, namely A5 (Block 5), A6 (Block 6), A7 (Block 7), A8 (Block 8), A11 (Block 7A ) and A1 (Block 1) with the highest score of 0.838. MAUT method can be used as an alternative method to perform calculations based on predetermined criteria so as to facilitate decision making.